2018
DOI: 10.1177/1075547018798119
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Consent: Rereading News on Four Climate Summits (2000-2012)

Abstract: This article examines if and how news media contribute to manufacturing consent by disabling ideological disagreement about established social structures underlying climate disruption. A critical discourse analysis reveals three discursive constructions emerging in two Belgian elite newspapers and one alternative news site during four climate summits (2000-2012). Despite advocating different policy approaches based on opposing ideological preferences, the newspapers were found to manufacture consent about thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…These results are in line with previous research on this topic that states that accounts on environmental change are often treated in a non-politicised way, adopting widespread scientific climate change discourses from Western countries (Pepermans and Maeseele 2018). This is certainly also the case in this study, as only few respondents applied scientific discourses on climate changes to local problems and issues, linking general climate change discourses to the environmental changes they perceived in their surroundings.…”
Section: Intraregional Differencessupporting
confidence: 91%
“…These results are in line with previous research on this topic that states that accounts on environmental change are often treated in a non-politicised way, adopting widespread scientific climate change discourses from Western countries (Pepermans and Maeseele 2018). This is certainly also the case in this study, as only few respondents applied scientific discourses on climate changes to local problems and issues, linking general climate change discourses to the environmental changes they perceived in their surroundings.…”
Section: Intraregional Differencessupporting
confidence: 91%
“…Previous quantitative research has indicated a link between levels of actor and viewpoint diversity (Masini et al, 2018), and qualitative studies have highlighted that alternative news outlets have a tendency to shed a different light on the news (Cissel, 2012;Pepermans & Maeseele, 2018). We expect that our results complement these findings, but the link between actor and viewpoint diversity in alternative news media has to be validated in future research.…”
Section: Conclusion and Discussionsupporting
confidence: 68%
“…Qualitative studies into the content of alternative news media show that their news coverage is different from the mainstream in terms of framing (Cissel, 2012), discourse (Pepermans & Maeseele, 2018) and journalistic role perceptions (Nygaard, 2019). The current literature focuses largely on the ways in which alternative news coverage is given form, how news stories are constructed and the general tone that is used to present certain issues.…”
Section: Introductionmentioning
confidence: 99%
“…How media and public discourses could shape perceptions of identity has been studied frequently using discourse analytical approaches by focusing on the "speaker positions" and "subject positions" constructed in public discourse (Benwell & Stokoe, 2006). In the field of climate change communication, some studies have built on this approach, or one of its variants (Boykoff, 2008;Pepermans & Maeseele, 2018;Weingart et al, 2000). However, despite many calls to focus on the subjectivities and identities portrayed, few studies, discourse-analytical and otherwise, have rigorously empirically investigated such portrayals in news coverage of climate change (Carvalho et al, 2017).…”
Section: Studying Mediated Identity Portrayalsmentioning
confidence: 99%